HUMOR : International Journal of Humor Research (De Gruyter Mouton, 1988)
HUMOR, the official publication of the International Society for Humor Studies (ISHS), was established over 25 years ago as an international interdisciplinary forum for the publication of high-quality research papers on humor as an important and universal human faculty. The journal publishes original contributions in areas such as interdisciplinary humor research, humor theory, and humor research methodologies.